THERMODYNAMIC PROPERTIES OF LIQUID ALLOYS OF NI-AL-M SYSTEMS: UDC 536.7 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
There has been lead the analysis of thermodynamic properties of liquid ternary Ni-Al-M alloys and the boundary systems, established by the method of calorimetry. The areas of easy amorphization for the specified ternary alloys were simulated with application of these data. It is shown, that all the investigated nickel superalloys are characterized by strong interaction between dissimilar atoms.
Keywords: -